Assessment of antidiabetic drug utilization and prescribing trends in outpatient care at a district general hospital in central Maharashtra - Kothari, Mandar; Giri, Reena R.; Abraham, Jijo P. (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Diabetes mellitus is a growing global health challenge with substantial morbidity, particularly in low- and middle-income countries like India. Rational prescribing of antidiabetic medications is essential to optimize glycemic control and reduce complications. Methods: A prospective observational study was conducted involving 605 diabetic patients. Prescriptions were analyzed using World Health Organization (WHO) prescribing indicators focusing on monotherapy versus combination therapy, drug classes prescribed, and adherence to essential medicines and generic prescribing. Results: The majority of patients were males (69.4%) aged 60-69 years (38%). The average number of antidiabetic drugs per prescription was 1.7. Monotherapy was prescribed in 31.4% of cases, while 68.6% received combination therapy. Metformin was the most commonly prescribed drug (95.9%), followed by Glimepiride (47.1%). Combination therapy of Glimepiride + Metformin was the most frequent regimen (43.3%). Insulin was prescribed in 6.6% of cases, predominantly biphasic insulin. All drugs were prescribed by generic names, with 98.3% from the National List of Essential Medicines (NLEMs). Conclusions: Metformin remains the cornerstone of antidiabetic therapy, with a clear preference for combination regimens, particularly Metformin plus Glimepiride, reflecting guideline-based practice for intensified glycemic control. The high rate of generic prescribing and use of essential medicines demonstrates adherence to rational prescribing principles. Ongoing prescription monitoring and patient-centered therapy adjustments are recommended to further optimize diabetes management.